A study on the performance and stability of hollow fiber supported liquid membranes using ionic liquid as bi-functional carriers for extraction of mercury / Ezalia Mohd Fauzi - Ezalia , Mohd Fauzi (2017)
Ionic liquids (ILs) are known as the replacement solvent over volatile organic compounds because of their novel properties. The purpose of this study was to evaluate the performance of Aliquat 336 on mercury (Hg) removal using hollow fiber liquid membrane (HFSLM) system. The system consists of a feed phase , a stripping phase and a membrane phase. In this study, the membrane mixture was prepared by mixing Aliquat 336 with [Emim][NTF2] as co-extractant/carrier. The prepared membrane mixture was used to extract Hg from the feed phase. In the feed phase, Hg solution was prepared in lower concentration which was 50 ppb. In addition, thiourea acted as the stripping agent to strip Hg from the membrane phase . The optimization of the process was carried out through investigation on the parameters: effect of concentration of co- extractants, stripping agent concentration, circulation time of extractants, flow rates of feed and stripping phase and the number or separation cycles. The findings pointed to the introduction of co-extractant was the key factor for Hg removal as it improved membrane stability and provided more Hg-complexes formation. Thus, the performance of HFSLM can be enhanced. An optimization study showed that the maximum Hg removal efficiency was achieved at 99.99% Hg removal with the used of 0.12M Aliquat 336 with 0.18M [EMIM][NTF2] as the extractants, 0.1M thiourea as the stripping agent with the flow rates of feed and stripping solution of 100 ml/min at 3-cycle separation.